Administration of intercollegiate athletics - Weight, Erianne A. 1981-; Zullo, Robert H. 1975- (Human Kinetics, 2015)
Bringing together some of the most knowledgeable professionals in the field of athletics administration, this text offers practical considerations and applications for financial operations, budgeting, marketing, corporate sponsorship, safety and risk assessment, ticketing, licensing and alumni relations.